2015
DOI: 10.1177/0363546515597485
|View full text |Cite
|
Sign up to set email alerts
|

Design and Testing of the Degree of Shoulder Involvement in Sports (DOSIS) Scale

Abstract: The DOSIS scale showed acceptable psychometric features and seems to be a valid instrument for shoulder assessment in athletes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 30 publications
0
18
0
1
Order By: Relevance
“…During the follow-up examination, the patients were evaluated using the following scores: the Subjective Patient Outcome for Return to Sports (SPORTS) score, [6][7][8] the Oxford Shoulder Instability Score (OSIS), 14 Subjective Shoulder Value (SSV), 17 Western Ontario Shoulder Instability Index (WOSI), 25 and the preinjury Degree of Shoulder Involvement in Sports (DOSIS) scale. 5 The SPORTS score was the primary outcome of this study. This is a score designed to address the ability to resume the preinjury sport level.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the follow-up examination, the patients were evaluated using the following scores: the Subjective Patient Outcome for Return to Sports (SPORTS) score, [6][7][8] the Oxford Shoulder Instability Score (OSIS), 14 Subjective Shoulder Value (SSV), 17 Western Ontario Shoulder Instability Index (WOSI), 25 and the preinjury Degree of Shoulder Involvement in Sports (DOSIS) scale. 5 The SPORTS score was the primary outcome of this study. This is a score designed to address the ability to resume the preinjury sport level.…”
Section: Methodsmentioning
confidence: 99%
“…The DOSIS scale 5 is a recently developed tool similar to the Tegner activity scale. 35 Its aim is to help the physician classify patients on the basis of their sport activity based on the specific involvement of the shoulder in that sport.…”
Section: Methodsmentioning
confidence: 99%
“…An open-source platform (https://drive.google.com) was configured to collect the responses anonymously. A total of 149 selected patients were contacted by telephone to present the research and to invite them to participate in the study and to fill in online the following self-reported outcome measures: the Degree of Shoulder Involvement in Sport (DOSIS) scale, 25 and the validated Italian versions of the Tampa Scale for Kinesiophobia (TSK) 26 and the Western Ontario Shoulder Instability index (WOSI). 27 The patients were asked to answer the DOSIS score retrospectively by recalling the period of time before the onset of shoulder instability (baseline score) and at follow-up examination (postoperative score).…”
Section: Data Collectionmentioning
confidence: 99%
“…Patients then obtain a score from 0 (no sport) to 10 (highdemand sport played by national/international level or professional athlete). 25 The DOSIS scale has been showed to have an adequate validity and responsiveness for sport-specific shoulder assessment in patients after surgery for anterior instability. 28 The TSK 26 is a widely used questionnaire for assessing pain beliefs and pain-related fear of movement/reinjury in the musculoskeletal field.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Add to the mix different surgical techniques and implants, and one can appreciate why discerning the signal through the noise is challenging. Some have worked on standardizing metrics for athletic activity specific to the shoulder, including the Degree of Shoulder Involvement in Sports (DOSIS) 2 and the Brophy shoulder activity score. 4 Return to play criteria have been elusive, and a recent systematic review of return to play criteria after surgical shoulder stabilization in athletes showed that time from surgery was the most commonly used criterion, reported in 90% of papers, with strength and motion being used in less than 20% of reports.…”
mentioning
confidence: 99%